Surface Proteins of Staphylococcus epidermidis - Foster, Timothy J. (Frontiers in Microbiology, 2020)
S. epidermidis is a ubiquitous commensal of human skin. The widespread use of indwelling medical devices in modern medicine provides an opportunity for it to cause infections. Disease causing isolates can come from many different genetic backgrounds. Multiply antibiotic resistant strains have spread globally. S. epidermidis has a smaller repertoire of cell wall anchored (CWA) surface proteins than S. aureus. Nevertheless these CWA proteins promote adhesion to components of the extracellular matrix including collagen, fibrinogen and fibronectin, and to the formation of biofilm. The A domain of the accumulation associated protein Aap can promote adhesion to unconditioned biomaterial but must be removed proteolytically to allow accumulation to proceed by homophilic Zn2+ dependent interactions. Mature biofilm contains amyloid structures formed by Aap the small basic protein Sbp. The latter contribute to the integrity of both protein and polysaccharide biofilm matrices. Several other CWA proteins are also involved in S. epidermidis biofilm formation.